Thailand at the margins : internationalization of the State and the transformation of labour - Glassman, Jim (Oxford geographical and environmental studies., 2004)
Jim Glassman addresses the role of the state in the industrial transformation of what was, before the economic crisis of 1997-98, one of Southeast Asia's fastest growing economies. Approaching this issue from a different angle than those dominating 1980s and 1990s debates about the role of states in East Asian growth, Glassman argues that the Thai state has been both proactive and interventionist in encouraging industrial transformation - contrary to what neo-liberals have asserted. - but at the same time has not been a 'developmental' state of the sort championed by neo-Weberian analysts of E.